COMMISSIVE SPEECH ACT IN THE PRESIDENTIAL CANDIDATE DEBATE OF R.I 2024 - Irma Suriyani Malau; Febrika Dwi Lestari Lumban Toruan; Fenty Debora Napitupulu (English Language Teaching Prima Journal (ELT), 2024)
This research aims to find the subtype of commissive speech acts used by presidential candidates and the most dominant subtype of commissive speech acts used by presidential candidates. The method used is the Descriptive Qualitative Method. The data of this research are utterances that contain commissive speech acts. The data source is the video of the presidential candidates' debate. The instruments of this research are observation and documentation. The researcher used the theory of Miles, Huberman & Saldana (2014) to analyze the data and obtained the results that in the presidential candidate debate, commissive subtypes were found, that is 5 subtypes of the nine commissive subtypes proposed by Searle and Vanderveken (1985), the five subtypes were 31 promises, one commit, one threaten, one accept and one pledge. The most dominant subtype in the presidential candidate debate is promising, with a percentage calculation of 88.5% promise, 2.8% commit, 2.8% threaten, 2.8% accept, and 2.8% pledge.